INDICADORES DE SAÚDE POSITIVA: UM ESTUDO COM EMPREGADOS EXPATRIADOS - Ribeiro, Paulo Eduardo (2009)
The expatriate studies, as much in how much international the national scope, normally deal with relative administrative aspects to the expatriation process, as, for example, the difficulties of adaptation of the individual and its family, as well as the damage that an unsuccessful program could bring for the organization. The objective of this study was to describe five psychosocial pointers of positive health (subjective well-being, well-being at work, perception of social support, perception of organizational support and optimism) in expatriated employees. A sample chosen for convenience was used, composed for 16people, being 8 of masculine sex and 8 of the feminine sex and that already they hadparticipated or they were participating of organizational programs of expatriation. The instrument of collection of data was a questionnaire of composed auto-fulfilling for eight measures that had surveyed the enclosed variable in the study (general satisfaction with the life, positive and negative affection, satisfaction in the work, involvement with the work, affective organizational involvement, perceptions of social and organizational support and optimism). Descriptive statistical analyses had been carried through, tested differences between averages, as well as calculated indices of correlation between variables. Results had disclosed that professionals expatriated had more chances to live deeply sensations affective positive of what negative in its experiences are of its native country, what allows to say that the expatriated ones tend the positive levels of very glad, happy, satisfied, much livened up and very well, very contented , then they had kept relatively preserved its subjective well-being. Also it was possible to observe that its bigger satisfactions with the life were not happened of the work and that they seemed to demonstrate to be satisfied with its interpersonal relations beyond presenting one strong affective entailing with its employer. Different result was gotten for involvement with the work disclosing that the tasks did not obtain to keep the expatriated one total absorbed by them during the period of expatriation. The study it also disclosed that the expatriated ones perceive to receive greater emotional support from its familiar ones, friends and relatives of what it has supported practical. How much to the perception of organizational support it was observed that they do not believe, unconditionally, in the support of the organization where they are inserted. The results had lightly shown despite the expatriated ones keep a positive expectation how much to the future, signaling an accented sense of optimism. It waspossible to also observe some significant correlations between the dimensions of SWB and well-being at work. On the basis of these results exist indications of positive health between the searched professionals, since they seem to be relatively well of good with the personal life and in the work, keeping medium beliefs of social and organizational support. The results of the study will be able to contribute for the understanding of the psychological picture of expatriated individuals e, at the same time, to offer one better conceptual recital for studious of the subject, as well as exciting in the managing reflections concerning action politics for the control of the psychic health of the employees who have participated or are participating of this type of organizational program.(AU)